2018
DOI: 10.3389/fcimb.2018.00421
|View full text |Cite
|
Sign up to set email alerts
|

Rv1288, a Two Domain, Cell Wall Anchored, Nutrient Stress Inducible Carboxyl-Esterase of Mycobacterium tuberculosis, Modulates Cell Wall Lipid

Abstract: Rv1288, a conserved hypothetical protein of M. tuberculosis (M.tb), was recently characterized as two-domain esterase enzyme by in silico study. In the present study, Rv1288 and its domains (Est and Lyt) were cloned individually from M.tb into E. coli for expression and purification. The purified rRv1288 and rEst proteins exhibited lipolytic activity with medium chain length esters as optimum substrates, while Lyt domain did not show enzymatic activity. However, presence of Lyt domain resulted in enhanced rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…Rv3091 protein overexpression allow recombinant Ms3091 to use lipids as a major carbon source, which further supports the role of this protein in bacterial intracellular survival, which agrees with the findings of previous studies (Zambrano and Kolter, 2005;Wang et al, 2008;Santucci et al, 2018a). These results were consistent with previous studies (Kumar et al, 2017;Maan et al, 2018;Kaur and Kaur, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Rv3091 protein overexpression allow recombinant Ms3091 to use lipids as a major carbon source, which further supports the role of this protein in bacterial intracellular survival, which agrees with the findings of previous studies (Zambrano and Kolter, 2005;Wang et al, 2008;Santucci et al, 2018a). These results were consistent with previous studies (Kumar et al, 2017;Maan et al, 2018;Kaur and Kaur, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, in this study, we examined the functional effects of MTS1338 by expressing it in non-pathogenic Mycolicibacterium smegmatis (basonym of Mycobacterium smegmatis , MSmeg), which shares about 79% nucleotide sequence identity with MTb and is very similar to it in terms of cell wall composition and metabolism, but lacks the MTS1338 gene [ 16 , 17 , 18 , 19 ]. Our results indicate that MTS1338 upregulates the enzymes responsible for the synthesis of the mycobacterial cell envelope and promotes the survival of MSmeg in macrophages, in which the MTS1338-expressing MSmeg induces phagosome maturation arrest and modulates the expression of pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Since esterases/lipases are involved in lipid degradation, this provides M. tuberculosis with an efficient source of energy and carbon for intracellular persistence (Maurya et al, 2018;Nazarova et al, 2019), as shown using recombinant strains (Lun and Bishai, 2007). Esterases/lipases are furthermore involved in remodelling of cell wall lipids, which have been shown to alter colony morphology, aggregation, and pellicle formation, thereby enhancing M. tuberculosis antibiotic tolerance and persistence (Singh et al, 2016;Kumar et al, 2017;Maan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%